Interaction of the Gut-Liver-Brain Axis and the sterolbiome with sexual dysfunction in patients with cirrhosis - Spencer C. Harris; Jasmohan S. Bajaj (Gut Microbes)
There is a complex interplay between the gut microbes, liver, and central nervous system, a gut-liver-brain axis, where the brain impacts intestinal and hepatic function while the gut and liver can impact cognition and mental status. Dysregulation of this axis can be seen in numerous diseases. Hepatic encephalopathy, a consequence of cirrhosis, is perhaps the best studied perturbation of this system. However, patients with cirrhosis have been shown to have increased incidence of other disorders of mental health which may be otherwise less clinically identifiable. Sexual dysfunction affects a large proportion of patients with cirrhosis and is associated with decreased quality of life. Screening for sexual dysfunction in patients with cirrhosis is often overlooked, and even when identified, treatment options are limited, particularly in patients with advanced liver disease. The mechanism by which patients with cirrhosis develop sexual dysfunction is multifactorial, but a key driver of this clinical manifestation is alterations in circulating sex hormones. In patients with cirrhosis, low serum sex hormones have been shown to be associated with higher mortality regardless of MELD score. The gut microbiome has been shown to have an immense metabolic capacity to metabolize steroid hormones. This “sterolbiome” has already been implicated in other disease processes and has been linked to low circulating sex hormones, suggesting a new mechanism by which sex hormones may be altered in disease states where the gut-liver-brain axis is disrupted. The aim of this review is to cover sex hormone changes and sexual dysfunction in cirrhosis, examine the gut microbiome and its metabolic capacity, particularly for steroid hormones, and consider how microbial changes using fecal microbiota transplant could modulate sexual dysfunction.